Voice Outcome following Acute Unilateral Vocal Fold Paralysis. (March 2013) - Young, VyVy N.; Smith, Libby J.; Rosen, Clark
Objectives: We assessed voice outcomes following unilateral vocal fold paralysis (UVFP). Methods: We performed a retrospective chart review of 72 patients with UVFP proven by laryngeal electromyography, including their Voice Handicap Index-10 (VHI-10) scores at presentation and at the study end point (at the return of vocal fold motion or before the decision regarding definitive treatment). Results: The average VHI-10 score on presentation was 26.9 of 40 (27.2 for patients who recovered motion and 26.7 for those who did not; p = 0.847). A recovery of vocal fold motion was experienced by 35% of patients, and 76.4% of patients underwent temporary vocal fold injection. For the patients who recovered motion, the average changes in VHI-10 score were −22.3 for those with injection and −11.4 for those without (p = 0.027). For patients without motion recovery, the average changes in VHI-10 score were −9.5 for those with injection and −0.8 for those without (p = 0.027). At the study end point, 84% of patients with return of motion had normal VHI-10 scores, in contrast to 21% of patients without motion recovery (p = 0.0009). Conclusions: A return of vocal fold motion is a vital determinant of voice outcome in patients with UVFP. However, despite recovery of vocal fold motion, 16% of patients in this study still had significant voice handicap. In contrast, 21% of patients without motion recovery had normal VHI-10 scores. This information can be used to counsel patients on voice outcome (precluding permanent treatment) with and without recovery of motion. There may be long-term voice benefit from early temporary vocal fold injection.